2017
DOI: 10.2514/1.c034095
|View full text |Cite
|
Sign up to set email alerts
|

F-16XL Simulations at Flight Conditions Using Hybrid Near-Body/Offbody Computational Fluid Dynamics

Abstract: The F-16XL flight vehicle has been used extensively to study the aerodynamics of medium-to high-angle-of-attack flight. Flight-test data, including surface pressures, are available for a wide range of flight conditions, allowing direct comparison between computational fluid dynamics and full-scale flight data. The most recent comprehensive study, made possible by NASA, was conducted by NATO Task Group AVT-113 and had participants from many different countries. One of the conclusions of the study was that unste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…An example is shown in Fig. 67 from Morton and McDaniel (132) using the KESTREL code (119) with AMR. Grids were adapted in both space and time, and a very fine resolution of the wing vortex flowfield was achieved.…”
Section: Three-dimensional Flows Sharp or Blunt-leading-edge Vorticementioning
confidence: 99%
“…An example is shown in Fig. 67 from Morton and McDaniel (132) using the KESTREL code (119) with AMR. Grids were adapted in both space and time, and a very fine resolution of the wing vortex flowfield was achieved.…”
Section: Three-dimensional Flows Sharp or Blunt-leading-edge Vorticementioning
confidence: 99%
“…The unsteady flow simulations from CAWAPI-2 indicated that more detailed unsteady work with finer grid resolution held out promise for simulating the FC-25 case, and it became the focus for the CAWAPI-3 investigations with hybrid RANS-LES modeling. [54]; left, butt line 153.5 computed time mean and variation pressure profiles and flight data [55].…”
Section: Rans Simulationmentioning
confidence: 99%
“…The CAWAPI-3 Assessment studied this question further with hybrid RANS/LES simulations [2], and Fig. 15 summarises one set of the results of Morton and McDaniel [54].
Figure 15. CAWAPI-3 Hybrid RANS/LES simulations, FC-25.
…”
Section: Slender Delta Wing Aircraftmentioning
confidence: 99%
“…Numerical simulation of flight-test conditions using delayed detached-eddy simulation has been performed. Simulations at flight conditions using hybrid near-body/off body CFD have been carried out as well (Boelens et al 2009;Lofthouse and Cummings 2017;Morton et al 2017). Nevertheless, the application of the Q-criterion algorithm so far has not been combined with the footprint of the streamline for the vortex development, in order to scrutinize the complete picture of the vortex dynamics.…”
Section: Introductionmentioning
confidence: 99%